Vaccination against viral hepatitis B in patients undergoing liver transplantation for hepatitis B-unassociated causes - V. E. Syutkin; A. A. Saliyenko; D. E. Syutkina; A. V. Chzhao (Трансплантология (Москва))
To study efficiency of molgramostim as an adjuvant in HBV vaccination we randomized 18 pts after OLT due to non-HBV causes. Nine pts received GM-CSF (150 mcg of sc 24 h before 1st dose of vaccine). Other 9 pts received only vaccine. Both groups of pts did not differ in sex, age, immunosuppression and received vaccine in double doses (40 mcg im) by similar way (0, 1 and 2 Mo). Anti-HBs titers were estimated in 3 Mo after the last dose of vaccine. High anti-HBs titer (>200 mME/ml) achieved 4 pts (44%) from the GM-CSF group and nobody from the control group (p=0.037) No serious adverse effects occurred. Conclusion: GM-CSF may be useful as an adjuvant in HBV vaccination after OLT.